1994
DOI: 10.1177/001440299406000503
|View full text |Cite
|
Sign up to set email alerts
|

Transition: Life-Span and Life-Space Considerations for Empowerment

Abstract: Transition is a process that should empower students, families, and communities. This article integrates literature from counseling, rehabilitation, multicultural education, and special education to explain the importance of life-span considerations, including a focus on preschool and early school years, and the importance of the life-space factors of family, culture, and community. Principles of intervention for empowerment promote transition interventions that are maximally under the control of the student, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 13 publications
0
32
0
1
Order By: Relevance
“…For many CLD families, transition is not a discrete time in life affecting only their child with a disability. The family as a whole is affected by the transition process and potential adult outcomes of their child (Marshak, Seligman, & Prezant, 1999;Szymanski, 1994). Evidence for this comes from a study by Rueda et al (2005) who found that among Latino mothers of children with developmental disabilities, the future well-being of their child was not considered to be separable from the overall well-being of their family.…”
Section: Person-family Interdependent Approach To Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many CLD families, transition is not a discrete time in life affecting only their child with a disability. The family as a whole is affected by the transition process and potential adult outcomes of their child (Marshak, Seligman, & Prezant, 1999;Szymanski, 1994). Evidence for this comes from a study by Rueda et al (2005) who found that among Latino mothers of children with developmental disabilities, the future well-being of their child was not considered to be separable from the overall well-being of their family.…”
Section: Person-family Interdependent Approach To Transitionmentioning
confidence: 99%
“…Despite an abundance of evidence supporting these practices, both focus almost exclusively on promoting the quality of life of the individual with the disability rather than emphasizing their overall family's quality of life (Kim & Turnbul, 2005). As noted earlier, transition is not a discrete time in life affecting only the individual with the disability; their family as a whole is often affected by the transition process and outcomes achieved by their young adult with a disability (Marshak, Seligman, & Prezant, 1999;Szymanski, 1994).…”
Section: Family-centered Adaptation Of Transition Practicesmentioning
confidence: 99%
“…This part of the study was included in NLTS2 because there has been an increase of selfconcept and self-determination training in the high school curriculum after IDEA amendments of 1997. Szymanski (1994) suggested that empowerment for students with disabilities grew from early childhood through adulthood. She pointed out that the life-span and life-space concepts grew from Donald Super's (1990) theory of career development as well as other related theories (Curnow, 1989;Osipow, 1983;Roe, Krumboltz, & Hershenson, 1990;Super, 1969Super, , 1990Szymanski;Szymanski, Turner, & Hershenson, 1992).…”
Section: Personality Developmentmentioning
confidence: 99%
“…Assurances are required by IDEA, Indicator 13 (CEC, 2006) that the IEP includes Education/Training, Employment, Independent Living, and Self-Determination goals (Szymanski, , 1994Wehmeyer, 1994). This suggestion entails professional development for staff, parents, and students.…”
Section: Step Grant and Transition Programs/practicementioning
confidence: 99%
See 1 more Smart Citation